The whales, they give themselves: conversations with Harry Brower, Sr. - Brower, Harry, Sr., author; Brewster, Karen, editor; University of Alaska Press, publisher (Colorado State University. Libraries, 2004)
The Whales, They Give Themselves is an intimate life history of Harry Brower Sr. (1924-1992), an Inupiaq whaling captain, artisan, and community leader from Barrow, Alaska. In a life that spanned the profound cultural and economic changes of the twentieth century, Brower's knowledge of the natural world made him an essential contributor to the Native and scientific communities of the North. Oral historian Karen Brewster builds upon Harry's stories with photos and cultural and historical background into this innovative and collaborative oral biography.
Introduction: Visiting -- Place called Utqiagvik -- Conversations: We Had Fun Anyway -- I Walked that All Over -- No Rest For the Wicked -- I Never Get Scared of Nothing -- A World of Possibilities -- He Gave Himself -- Epilogue: Through Other Eyes -- Appendix: Outside Looking In -- Endnotes.
Keywords: Brower, Harry, 1924-; Inupiat -- Alaska -- Barrow -- Biography; Whaling masters -- Alaska -- Barrow -- Biography; Whaling masters -- Alaska -- Barrow -- Biography; Whaling masters -- Alaska -- Barrow -- Biography; Barrow (Alaska) -- Social life and customs